Komposisi Musik Katarsis Vokal - Hidayat, Tania Rahmawati; Apriani, Arni; Setiaji, Deden (CV. ITTC INDONESIA, 2025)
This article explores the creation of the contemporary music composition Katarsis Vokal, which utilizes the human voice as the primary instrument. The work was born from the need for emotional expression through the exploration of non-conventional sounds such as humming, heavy breathing, and screaming. The creative process included stages of preparation, vocal exploration, dramaturgical structuring, and verification of the work. The results show that free vocal exploration can serve as both an artistic medium and a space for emotional catharsis for both the creator and the audience. In addition to contributing to the development of contemporary music, this work emphasizes that the human voice is the most authentic instrument for conveying deep emotions.